2023
DOI: 10.1590/2526-8910.ctoao269035092
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on “what matters”: the Occupation, Capability and Wellbeing Framework for Occupational Therapy

Abstract: Introduction Critical occupational therapists have challenged models from the Global North that have dominated occupational therapy and informed ableist practices focused on appraising dysfunctions, classifying deviations from bodily “norms”, and remedying individuals’ “deficits” in performing three occupations (self-care, productive, leisure). This indicated the need for a new conceptual framework; one grounded in research evidence derived from a diversity of people and contexts. Objectives To outline the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Participation in an occupation, such as an animal-assisted and nature-based activity, that the individual perceives meaningful, as a complement to ordinary care and social services, can be an important step in the rehabilitation process by creating favourable conditions in everyday life. This is in line with Wilcock and Hocking (2015) and Hammell (2020) who report on moving forward towards health and well-being, education or job training. Participating in animal-assisted and nature-based interventions increases self-esteem and self-confidence (Hultsjö & Jormfeldt, 2022) and probably also the perceived sense of coherence (Antonovsky, 1993) although, as far as we know, this has not been quantitatively measured.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participation in an occupation, such as an animal-assisted and nature-based activity, that the individual perceives meaningful, as a complement to ordinary care and social services, can be an important step in the rehabilitation process by creating favourable conditions in everyday life. This is in line with Wilcock and Hocking (2015) and Hammell (2020) who report on moving forward towards health and well-being, education or job training. Participating in animal-assisted and nature-based interventions increases self-esteem and self-confidence (Hultsjö & Jormfeldt, 2022) and probably also the perceived sense of coherence (Antonovsky, 1993) although, as far as we know, this has not been quantitatively measured.…”
Section: Discussionsupporting
confidence: 90%
“…Finding meaning through being engaged in occupations may positively contribute to social change in everyday life, and is closely related to mental health and well‐being (Hammell, 2020; Wilcock & Hocking, 2015). Animal‐assisted interventions are structured and goal‐oriented activities that integrate domestic animals in healthcare and social work (Beetz, 2017; IAHAIO, 2018), while nature‐based interventions provide activities in a horticultural and/or wild natural environment (Annerstedt & Währborg, 2011; Hansen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In occupational therapy literature, occupations are defined as activities which occupy a person's time (Jackman, 2014) and contribute to their overall wellbeing (Hammell, 2017;Han et al, 2016). Research has identified a positive association between engaging in meaningful occupations and overall health and wellbeing (Hammell, 2020;Hocking, 2019;Morgan-Brown et al, 2018;Neal et al, 2020;Wilcock & Townsend, 2019). Unlike participation which must be active, engagement can be passive and is characterised by 'the degree to which an individual involves him/herself' (Black et al, 2019;Jackman, 2014, p. 242), becoming deeply invested in the occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the theoretical understanding that person-centred care is best practice to support older adults living with dementia in RACHs (Laver et al, 2016), there has been a noticeable gap between theoretical understanding and clinical practice in RACHs (Laver, 2016). This inconsistency is evident in the limited opportunities for meaningful engagement available to residents with dementia and contributes to the issue of occupational injustice among older adults living with dementia in RACHs (Hammell, 2020;Morgan-Brown et al, 2018;Wilcock & Townsend, 2019). Research since the early 2000s reflect that residents can spend 17 or more hours in bed each day (in a study conducted by Bates-Jensen et al, 2004 across 15 RACHs) or spend most their time unoccupied and doing nothing; a reality that is worse for older adults living with dementia as they are the least likely to be engaged in care settings (Hill et al, 2010;Kolanowski & Litaker, 2006).…”
Section: Introductionmentioning
confidence: 99%